Diet and supplement assessment in a Brazilian urban population - Alessandra Gaspar Sousa; Teresa Helena Macedo da Costa (Universidade de São Paulo, 2021)
ABSTRACT OBJECTIVE: To assess total usual nutrient intakes from foods and dietary supplements by age, sex, physical activity, and nutritional status, and to compare usual nutrient intakes to the Dietary Reference Intakes among non-users and users of dietary supplements in an urban population. METHODS: Cross-sectional population-based survey with 506 adults conducted in the city of Brasília, Brazil, using 24h food recalls. The 24-HR was collected on two nonconsecutive days, for which individuals reported all food, supplements, and beverages consumed in the previous 24 hours. The estimates of mean and the distribution percentiles were adjusted to reflect usual nutrient intake using the Iowa State University method. The prevalence of inadequate micronutrient intake was estimated according to sex using the Estimated Average Requirement (EAR), and values above the Tolerable Upper Intake Level (UL) were also considered. Also, a comparison was made of the total mean usual intake between supplement users and non-users according to BMI and physical activity. RESULTS: The total mean usual dietary intake was significantly higher among users than non-users of dietary supplements (p ≤ 0.02). Dietary supplement use increased intakes of nutrients and decreased prevalence of inadequacy according to sex, with only small (typically < 13%) increases in the population exceeding the Tolerable Upper Intake Level. There was a significant interaction between physical activity and BMI categories with supplement use. CONCLUSIONS: The population that consumes food supplements comprises individuals with more advanced age, female, normal BMI, and physically active. Our findings show that the use of supplements appears beneficial to attain nutrient adequacy. Careful monitoring of intake from food and supplements is recommended, and the statistical methods must be powerful enough to achieve relevant information.